Modern Statistical Aspects of the Analysis of Hydrochemical Loads in Water Bodies - Anatoly P. Lepikhin A. P.; Sintsova, Tatyana N. (Recent Developments in Chemistry and Biochemistry Research Vol. 6, 2024)
The purpose of the study is to analyze the correctness of statistical estimates of the hydrochemical characteristics of water bodies used in current regulatory documents on the regulation of technogenic impact on water bodies. The consistency of statistical estimates of arithmetic means, medians and dispersions of both theoretical and practical distribution functions of hydrochemical characteristics in water bodies is considered. The analysis of the consistency of the estimates was carried out using the licensed software product Mathcad 13. As a result of the calculations, it was shown that the nature of the variability of the hydrological regime of the receiving watercourse plays a decisive role in the constancy of the arithmetic average values. In this case, when the coefficient of variability of watercourse discharge Cv > 1, these estimates become unreliable, and the errors in their estimates do not decrease with increasing sample size. The dependences of the root-mean-square error of arithmetic means, medians and dispersions for various distribution functions of the flow rates of the watercourse and discharged wastewater were analyzed. It was shown that median estimates were characterized by greater statistical stability than estimates based on arithmetic mean characteristics. The incorrectness of the current regulatory system was demonstrated by the example of the rationing of suspended substances. It was proposed to reduce the errors in determining the concentration of suspended substances by at least an order of magnitude or to increase the allowable excess of their content in the control area over the background levels.